KAJIAN PENGGUNAAN PUPUK MIKRO CU TERHADAP PRODUKSI DAN PENDAPATAN USAHATANI KENTANG DI KECAMATAN LEMBANG, BANDUNG - NURAWAN, AGUS (Agrotrop : Journal on Agriculture Science; Vol 1 No 2 (2011), 2012)
Study on Effect of Cu Fertilizer against Production and Income of Potato Agribussines in Lembang Bandung. The study of the effect of Cu micro fertilizer on potatoes plant was conducted at Cikahuripan Village, Manoko with the altitude of 1,200 meters above sea level in Lembang West Java. Method used in this experiment was Randomized Blok Design (RBD) with 5 level dosages of Cu/plant i.e. 1) 0 ppm Cu (Control), 2) 3 ppm Cu/plant, 3) 20 ppm Cu/plant, 4) 30 ppm Cu/plant, and 5) 50 ppm Cu/ plant, all with 8 replication. The Cu fertilizer used in this experiment were: CuS04.4H2O with 23% concentration in form of solution. Two variables observed in this experiment were: tuber diameter, fresh condition, and Revenue and Cost Ratio (R/C ratio) analysis. The objective of the study was: to observe the effect of Cu micro fertilizer on the growth and the productivity, along with the revenue and the benefit and cost ratio. The results showed that, with the dosage 3 ppm Cu/plant, shows a positive effect of productivity, and the dosage 20 ppm Cu/plant yields optimum productivity i.e. 429.75 g/plant. The dosage greater than 20 ppm showed decreasing in productivity e.g. with 50 ppm Cu/plant caused physiological and metabolism disorder to the plant. From the labor cost and Revenue Analysis we noted the following result: 1) with the treatment of 20 ppm (C treatment) the revenue in Rp73,670,400 and R/C ratio of 1.82, 2) with the treatment of 3 ppm Cu/plant yield Rp 71,013,600 with R/C ratio of 1.82. 3) with the treatment of 40 ppm/plant yield Rp 63,874,800 with the R/C of 1.52. 4) with the treatment of 0 ppm (Control) the revenue yield Rp 57,812,400 with the R/C ratio of 1.52.
Keywords: potato, Cu micro fertilizer, farm analysis